Implementation of Ad-Hoc Protocol On Tandem Multihop Wireless Network - Agussalim Agussalim; Dhian Satria Yudha Kartika; Ani Dijah Rahajoe (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2022)
The utilization of Internet of Things (IoT) technology, especially in remote areas, is still relatively low, even though the technology is required to implement smart farming or smart villages, which aims to improve the quality of life of people in rural areas. The high investment cost for IoT networks that still use cellular networks or Wi-Fi is one of the causes of the slow implementation of this technology. Our previous research has developed an alternative network for IoT devices in remote areas with the concept of a Tandem Multihop Wireless Network focusing on developing simple message scheduling. This research focuses on implementing ad-hoc routing protocols in tandem with multi-hop wireless to analyze the advantages and disadvantages of the protocol. Each sensor periodically sends data to the monitoring server via IoT devices on each tower. The scenario was implemented using MININET-WIFI. Evaluations were carried out to determine delivery probability, latency average, and jitter. In general, the two Ad-Hoc protocols tested, namely OLSR and BATMAN, had the same performance when the data sent was 1 MB, but when the data size was increased to 2 MB, the OLSR routing protocol on several nodes had better performance than BATMAN.